Censorship detected in IR (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2026-2322. Severity: critical. Confidence: 90%